Penyalahgunaan Keadaan (Misbruik Van Omstandigheden) dalam Perjanjian Pengikatan Jual Beli (Studi Putusan Nomor 143/PDT/2016/PT. DKI) - Tasya Veronika Anrori Ginting; hasim purba; mahmul Siregar (CV Rewang Rencang, 2025)
Abuse of circumstances (misbruik van omstandigheden) is a jurisprudential doctrine not yet regulated in Indonesian written law. A normative juridical research method was used to analyze Decision Number 143/PDT/2016/PT. DKI. Research findings indicate characteristics of abuse of circumstances include special circumstances and awareness. Sale and Purchase Binding Agreement Deeds containing abuse of circumstances can be declared null and void. The Panel of Judges ruled that the use of absolute power of attorney exploiting deteriorating economic conditions constitutes abuse of circumstances causing defective consent. Legal reform of the Civil Code is needed to regulate this doctrine to provide legal certainty and protection.